O desvelar das contradições do modelo de descentralização : as interfaces escalares na conformação do sistema único de saúde em Sergipe - Santos, Ana Rocha dos (2008)
In the conduction of the Brazilian politics, the centralization and decentralization models, in the contexts of the situation in which they are enrolled, have been presented in the apparent as opposites, and they indicate in their essence strategies of space control in the different interfaces of the unequal geographical development of the capitalism. The politics of decentralization of the last governments (starting from the end of the 80s) is associated to the crisis of the development model and the exhaustion of the supplying State, what gives it the attribute of potentializing of the strategies to promote the development and the redefinition of the size of the State. The speech of the decentralization is affirmed by identifying it with emancipation and and democratization, resultant of fights and social conquests of rights and citizenship, what means ideologically, a positive reinforcement for the elaboration of neoliberal public politics. In this context it is enrolled the politics of health (SUS), whose historical roots are connected in the democratic fights of the 80s, at the same time in that the neoliberalism was settled in the country. Seemingly, it is revealed a politics in the wrong way of the neoliberal project, but the dialetical glance undresses the apparent and exposes the contradictions of the (des) centralizing politics of the State. The reading of the reality starting from the category of the totality allows the understanding that the politics of decentralization of the health and the invigoration of the local spaces (the municipal districts) was not only an answer to the financial crisis and the governmentality problems. The decentralization politics has in the municipal districts the strategy to the accomplishment of the located territorialy development, as an instrument of the flexible accumulation that acts in the reformulation of the scales functionalities to adapt them to the deregulation of the markets. The area is valued, fetished as the place to solve the structural crisis of the money, in which the crisis of the State is just a symptom of its terminality. The scalar redraw printed by the decentralization was studied in this research, accomplished in Sergipe starting from the hypothesis that the democratic speech present in the politics of decentralization of the health masks the deprived appropriation of the services and actions of health in the ambit local/nacional/global, through a selective and excluding nested net. For it, it also competes, the patrimonial treatment of the public thing that unchains disputes and takes out the responsibility of the municipal and state governments to the attendance of the health needs of the population. To the Geography it fits the (un) concealing of the reality through the space reading, to the unveiling of the strategies contradictions of the space control for the money.